The effectiveness of one “physical education minute” during lessons to develop concentration in 8- to 10-year-old schoolchildren - Polevoy, Georgiy; Cazan, Florin; Padulo, Johnny; Ardigò, Luca Paolo (Frontiers in Sports and Active Living, 2023)
The demands of the school day, which includes multiple lessons, require sustained attention from students, which can be challenging, especially for young children. Concentration of attention is a critical cognitive function that impacts learning. This study involved 129 healthy schoolchildren aged 8-10 from a regular secondary school in Kirov, Russian Federation, spanning grades 2 and 3. A “physical education minute” (PEM), consisting of various physical exercises, was introduced during the middle of a regular lesson for the experimental group (EG), while the control group (CG) continued with their regular studies. Concentration and attention were assessed using the Bourdon test before and after the PEM. The Bourdon test results indicated a significant decrease in concentration for the CG during the lesson (p<0.001), while the EG exhibited a significant improvement in concentration after the PEM (p<0.001). The effect size was large, demonstrating a substantial impact of the physical activity break on concentration. The study concludes that implementing a set of exercises as a PEM in the middle of a lesson significantly improves the concentration of students aged 8-10. This research underscores the effectiveness of integrating short physical activity breaks into the daily classroom routine, ultimately benefiting students' attention, learning and overall educational experience. Further research could explore additional factors affecting concentration and the long-term effects of physical education minutes on cognitive development.